Distribution and transfer of organochlorines in Adelie penguins (Pygoscelis adeliae) in a breeding season - Subramanian, An.; Tanabe, Shinsuke; Hidaka, Hideo; Tatsukawa, Ryo (1986)
P(論文) PCBs and p, p'-DDE were analysed in the subcutaneous fat (SCF), abdominal fat (AF), muscle, liver, bone, brain and an egg sample of Adelie penguins collected from Antarctica during the breeding season of 1981. PCBs and DDE were largely retained in the fat-rich tissues of Adelie penguins. With advancement of starvation and resulting shrinkage of fat reserves, linear increase in the concentrations of both the compounds in the fat tissues and some sort of redistribution to other body parts were observed. Excretion via eggs, of organochlorines, was not found to be significant in Adelies. Elimination rates of all PCB isomers and congeners as well as DDE were found to be more or less the same. Loss and gain rates and biological half-life (BHL) of both the compounds were calculated on the basis of the feeding habits of Adelie penguins. BHL was found to be longer and loss rate lower in the case of DDE than PCB, indicating a faster clearance rate of the latter. departmental bulletin paper